Os saberes docentes específicos da matemática em cursos de segunda licenciatura em Matemática à distância: uma análise a partir dos seus documentos orientadores - Guedes, Simone Batista (2023)
The objective of this research was to identify, in three second degree courses in Mathematics, from three Higher Education institutions, in the Distance Education modality, how the teacher is being trained to work in the final years of Elementary and High School, according to with the documents that support them, regarding teaching knowledge – Content Knowledge, Pedagogical Knowledge, Technological Knowledge and Specialized Knowledge, with a focus on specific knowledge of Mathematics. The question that guided this work was: How is the formation of Mathematics teachers in the second degree courses, in the distance modality, of three higher education institutions with headquarters in the states of São Paulo and Paraná, mischaracterized, in the perspective of the documents that support them, in relation to teaching knowledge: Content knowledge; Pedagogical Knowledge; Technological knowledge and specialized knowledge, with a focus on Mathematics? To answer this question, studies on teaching knowledge were supported, mainly those developed by Lee Shulman, Mishra and Koehler and Ball, Thames and Phelps. A methodology with a qualitative approach, of the documentary type, was adopted. The analyzes were performed using Content Analysis techniques, proposed by Laurence Bardin. The results showed that despite the specific knowledge of mathematics being developed in the courses, knowledge related to the specific contents of mathematics prevails, which often do not relate to mathematics for teaching in the final years of elementary school and high school and even less, with technological knowledge related to the teaching of mathematics. It is believed, then, that the results of this work can: a) contribute to actions to regulate this type of course, considering the amalgam of knowledge that constitutes mathematics teaching; b) lead to reformulations of these courses; c) and also subsidize continuing education actions for teachers trained through them